The distributive characteristics of vola pressure upon the ground for male high-jumpers at taking off during the Fosbury Flop - Jin, L.; Zhang, Q.; Yin, W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Using the RS scan pressure insoles, the author examined the distributive characteristics of vola pressure on the ground for five high-jumpers from the Shandong province. The author applied the theory of sports biomechanics to this project, which investigates the peak value of vola intensity of pressure and the path of the center of pressure that can influence the take-off. The analysis of the take-off technical movements in the present study reveals the vola pressure distribution characteristics and patterns and provide a theoretical basis for the athletes on how to improve their techniques and how to avoid injury. Methods The author tests and analyzes five outstanding Shandong high-jumpers` distribution characteristics of the peak value of vola intensity of pressure and the track of the pressure center at 8 vola zones on the take-off foot at the take-off moment. The 8 zones are named T1, M1, M3, M5, V1, V2, H1, H2, which are each 2cm by 2cm in size. T1: the first toe joint; M1: the first metatarsophalangeal joint; M3: the third metatarsophalangeal joint; M5: the fifth metatarsophalangeal joint; V1: the tarsometatarsal joint, between the 1st cuneiform bone and the 1st metatarsal bone, medial transverse arch. V2: between the cuboid bone and the 4th metatarsal bone, lateral transverse arch. H1: underside medial calcaneus H2: underside lateral calcaneus. Using the JVC-9800 digital vidicon and Rsscan measurement system of vola pressure distribution, the author captures the take-off movements of the 5 high-jumpers, who are wearing Rsscan pressure-induced insoles and data collective instruments. Each athlete repeats the successful movement 5 times. The camera shot signals and vola pressure distribution measurement signals were recorded at the same time. The data was analyzed with Semi kinescope analysis software and Rsscan software package. Results / Conclusions Of the eight zones of the 5 athletes` plantar surface, the maximum pressure peak values appear in the H1 zone. The high pressure peak value of H1 shows the high the speed of run-up. It leads to the braking effect, larger ground stress and the higher speed of turning angles. When training, the athlete should consciously increase the take-off leg`s pressure on the ground so as to increase the braking frictional force and improve sustained counterforce upward on the take-off leg. The medial longitudinal arch is above the lateral longitudinal arch, so the pressure peak value of V1 is higher than that of V2. All the minimum pressure peak values of the five athletes` eight zones are in the V1. In the M1, M3 and M5, the pressure peak values rank in the descending order of M1, M3 and M5. In the process of rotation with the metatarsophalangeal joint as its fulcrum, the human center line is through the ankle and the first metatarsophalangeal joint; thus, the focal point lies on the first metatarsophalangeal joint. Therefore, the pressure peak value in M1 zone is the largest. In the eight tested zones, the reasonable order of pressure peak values should be: H1, M1, H2, M3, T1, M5, V2 and V1. When the high-jumpers are in the course of take-off, pressure peak values of eight zones are interconnected. As for the first-class and the second-class high-jumpers, the pressure peak values of the take-off foot in the eight zones mainly differ in H1, M1 and M3 zones. In terms of the extent of the horizontal and vertical axis, from the heels to the half soles, the pressure center tracks of the first-class athletes are greater than those of the second-class athletes.